2008
DOI: 10.1038/ncpcardio1278
|View full text |Cite
|
Sign up to set email alerts
|

Fibrates and future PPARα agonists in the treatment of cardiovascular disease

Abstract: Statins lower cardiovascular risk in patients with diabetes; however, as these patients are at higher risk than other cardiovascular patients, statins merely decrease coronary event rates to the level seen in untreated nondiabetic individuals at risk for cardiovascular disease, indicating the existence of substantial residual risk. One reasonable explanation resides in the fact that statins have only limited effectiveness on hypertriglyceridemia and low HDL cholesterol, and they do not normalize the LDL size-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 80 publications
2
107
0
1
Order By: Relevance
“…In the case of fenofibrate, the presence of these correlations is a logical consequence of the involvement of FFA in the development of insulin resistance in both men and women [26], as well as the role of endogenous ligands for PPAR-a [27]. Finding that a similar reduction in FFA was induced by simvastatin is in agreement with the hypothesis that the molecular mechanisms of the action of statins and fibrates partially overlap [28,29]. An inhibitory effect of simvastatin-induced inhibition of protein prenylation on the activity of glucose transporter 4 [30], responsible for insulinregulated glucose transport into the cell [31], may explain why, despite a reduction in FFA, simvastatin did not improve insulin sensitivity.…”
Section: Prace Oryginalnesupporting
confidence: 67%
“…In the case of fenofibrate, the presence of these correlations is a logical consequence of the involvement of FFA in the development of insulin resistance in both men and women [26], as well as the role of endogenous ligands for PPAR-a [27]. Finding that a similar reduction in FFA was induced by simvastatin is in agreement with the hypothesis that the molecular mechanisms of the action of statins and fibrates partially overlap [28,29]. An inhibitory effect of simvastatin-induced inhibition of protein prenylation on the activity of glucose transporter 4 [30], responsible for insulinregulated glucose transport into the cell [31], may explain why, despite a reduction in FFA, simvastatin did not improve insulin sensitivity.…”
Section: Prace Oryginalnesupporting
confidence: 67%
“…Outcome trials of PPARalpha agonists have shown decreased cardiovascular morbidity in patients with diabetes and in those with the metabolic syndrome. In addition, plaque progression is diminished, and there is a decrease in both microvascular (including diabetic nephropathy and retinopathy) and macrovascular complications (reviewed by Staels et al, 2008). Two trials worth mentioning are the FIELD study and the DAIS study.…”
Section: Fibratesmentioning
confidence: 99%
“…1 These disorders are characterized by abnormalities in glucose and lipid metabolism, putting patients at increased risk for macro-and microvascular complications. 2 Although statin treatment, which primarily targets elevated plasma low-density lipoprotein (LDL)-cholesterol levels, lowers cardiovascular morbidity and mortality in patients with type 2 diabetes, 3 it is increasingly clear that a significant residual cardiovascular risk remains in these patients, [3][4][5] which is partly attributable to the typical atherogenic lipoprotein profile (ALP) characterized by hypertriglyceridemia and low high-density lipoprotein (HDL)-cholesterol concentrations. 6 Post hoc analysis of statin trials, such as PROVE-IT TIMI 22, have identified plasma triglycerides as a determinant of cardiovascular risk in patients achieving LDL-cholesterol goals.…”
mentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor ␣ agonists, such as the currently used fibrates, are drugs used in the treatment of hypertriglyceridemia. 3 These compounds are potent downregulators of apoCIII expression. 11 Interestingly, fibrates have been found to be most efficacious in those patients with the ALP associated with the metabolic syndrome and type 2 diabetes, 3 and these novel findings regarding apoCIII may provide a mechanistic explanation for these effects of peroxisome proliferator-activated receptor ␣ ago-nists.…”
mentioning
confidence: 99%